Repurposed texts and translation: the case of José Saramago’s El Silencio del Agua in Turkish - Gökce Vaz de Carvalho, İmren (2021)
This article focuses on the Turkish translation of a picturebook by Portuguese Nobel laureate author José Saramago, first published in 2012 after the author’s death. The source text for this translation was a Spanish picturebook for children, El Silencio del Agua, created by the Barcelona-based publisher Libros del Zorro Rojo in 2011 by publishing an excerpt from the Spanish translation of Saramago’s book As Pequenas Memórias (Las Pequeñas Memorias, 2007) as an illustrated stand-alone children’s book. This represents a repurposing of the work since both As Pequenas Memórias and Las Pequeñas Memorias targeted an adult readership. The Turkish picturebook, translated from the “original” Spanish picturebook, was published with the same illustrations by Manuel Estrada. Meanwhile, the Portuguese work As Pequenas Memórias had also been translated into Turkish, much before the publication of the picturebook, by another translator directly from Portuguese. In this study, the two Turkish translations (the Turkish picturebook and the equivalent passage from the Turkish translation of the ultimate source text) are compared to find out how repurposing a text originally written for adult readership as children’s literature influences its translation. The case of El Silencio del Agua in Turkish also raises interesting questions about how the cultural status of author and translator affects translation, as well as touching on current debates taking place in the spheres of children’s literature, retranslation, indirect translation, and reception studies. KEYWORDS: Repurposed Texts, Retranslation, Indirect Translation, Picturebook, Children’s Literature